93 Practical Outpatient Pharmacotherapy for Alcohol Use Disorder. (12th March 2019) - Kim, Youngjung; Hack, Laura M; Ahn, Elizabeth S; Kim, Jungjin
Abstract: Alcohol use disorder (AUD) is commonly encountered in clinical practice. A combination of psychosocial intervention and pharmacotherapy is the cornerstone of AUD treatment. Despite their efficacy, safety and cost-effectiveness, clinicians are reluctant to prescribe medications to treat individuals with AUD. Given the high rate of relapse with psychosocial intervention alone, increasing patient access to this underutilized treatment has the potential to improve clinical outcome in this difficult-to-treat population. Herein, we provide practical pharmacotherapy strategies to improve treatment outcome for AUD. We review the efficacy and side effects of both on- and off-label agents with a particular focus on clinical applicability. Recommendations are supported by findings from randomized controlled trials (RCT) and meta-analyses selected to be representative, where possible, of current treatment guidelines. The goal of this paper is to help readers use pharmacotherapy with greater confidence when treating patients with AUD.